Respon Pertumbuhan, Hasil Dan Ketahanan Cabai Terhadap Phytopthora capsici L. Yang Diaplikasikan Kompos Yang Diinokulasi Trichoderma spp Dan Bakteri - Fenny Salomina Jensanura Asyerem (Agrotek, 2015)
The research aims to study the effect of compost formulas given Trichoderma spp, and bacteria on growth and yield of chilli variety Hot Marconi and resistance to P. capsica L. PCSTL2. The experiment was conducted in laboratory of Balitro and greenhouse at Cikabayan, IPB in May to November 2011. The experiment pot used Randomized Block Analysis with 3 replicated. Formula compost as treatment are (A). Manure + A. conyzoides var hirtum (Lam) + sago residue + Trichoderma spp, (B). Manure + A. conyzoides var hirtum (Lam) + sago residue + bacteria, (C). Manure + T. diversifolia (Hamsley) A. Gray + sago residue + Trichoderma spp, (D). Manure + T. diversifolia (Hamsley) A. Gray + sago residue + bacteria, (E). Manure + A. conyzoides var hirtum (Lam) + sago residue + Trichoderma spp + bacteria, (F). Manure + T. diversifolia (Hamsley) A. Gray + sago residue + Trichoderma spp + bacteria. The results showed that treatment of formula compost significant improve on growth and yield of chilli and the incidence disease against P. capsici L. PCSTL2 and first harvest chilies. Although the treatment of compost formula showed lower growth and higher incidence of disease but is able to increase the yield of chili than control.